2021
DOI: 10.1371/journal.pone.0259134
|View full text |Cite
|
Sign up to set email alerts
|

Accelerative action of topical piperonylic acid on mice full thickness wound by modulating inflammation and collagen deposition

Abstract: Epidermal growth factor (EGF) promotes cell growth, proliferation, and survival in numerous tissues. Piperonylic acid, a metabolite present in peppers (Piper nigrum L. and Piper longum L.), can bind to the epidermal growth factor receptor (EGFR) and induce an intracellular signaling cascade leading to the transcription of genes responsible for these actions, especially in keratinocytes. These cells are fundamental in maintaining cutaneous homeostasis and are the first to be damaged in the case of a wound. Thus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 33 publications
(47 reference statements)
0
3
0
Order By: Relevance
“…For instance, 2-furancarboxylic acid obtained by dehydrogenation of furfuryl alcohol is a very important chemical generally used as a food preservative and flavoring agent in the food industry, as a fungicide and a bactericide, and as an intermediate in the pharmaceutical industry . Similarly, piperonylic acid, obtained by dehydrogenation of piperonyl alcohol, showed several pharmacological applications such as anticancer, anti-inflammatory, antidiarrheal, antioxidant, etc. , Likewise, 1-adamantane ethanol on dehydrogenation gives 1-adamantane acetic acid, which shows antiviral properties . We were delighted to see that our catalyst could convert furfuryl alcohol, piperonyl alcohol, and 1-adamantane ethanol to their corresponding acid in 36 (Table , Entry 2m ), 53 (Table , Entry 2n ), and 32% (Table , Entry 2p ) yields, respectively, with the liberation of hydrogen gas.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, 2-furancarboxylic acid obtained by dehydrogenation of furfuryl alcohol is a very important chemical generally used as a food preservative and flavoring agent in the food industry, as a fungicide and a bactericide, and as an intermediate in the pharmaceutical industry . Similarly, piperonylic acid, obtained by dehydrogenation of piperonyl alcohol, showed several pharmacological applications such as anticancer, anti-inflammatory, antidiarrheal, antioxidant, etc. , Likewise, 1-adamantane ethanol on dehydrogenation gives 1-adamantane acetic acid, which shows antiviral properties . We were delighted to see that our catalyst could convert furfuryl alcohol, piperonyl alcohol, and 1-adamantane ethanol to their corresponding acid in 36 (Table , Entry 2m ), 53 (Table , Entry 2n ), and 32% (Table , Entry 2p ) yields, respectively, with the liberation of hydrogen gas.…”
Section: Resultsmentioning
confidence: 99%
“…62 Similarly, piperonylic acid, obtained by dehydrogenation of piperonyl alcohol, showed several pharmacological applications such as anticancer, anti-inflam-matory, antidiarrheal, antioxidant, etc. 63,64 Likewise, 1adamantane ethanol on dehydrogenation gives 1-adamantane acetic acid, which shows antiviral properties. 65 We were delighted to see that our catalyst could convert furfuryl alcohol, piperonyl alcohol, and 1-adamantane ethanol to their corresponding acid in 36 (Table 1, Entry 2m), 53 (Table 1, Entry 2n), and 32% (Table 1, Entry 2p) yields, respectively, with the liberation of hydrogen gas.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Due to its characteristics of unique mechanism of action, novel scaffolds, and easy derivation, the natural products have always been a valuable source for lead compounds discovery in agricultural chemistry. Piperonylic acid is an aromatic acid mainly found in black pepper ( Moreira et al, 2021 ). Lots of research results revealed members of the piperonylic acid family had a range of biological activities and were further developed into a commercial drug and widely used in the field of medicine, such as oxolinic acid ( Yamazawa et al, 2021 ; Boycov et al, 2022 ; Quan et al, 2022 ), kakuol ( Jang et al, 2020 ; Matsumoto et al, 2020 ; Sui et al, 2020 ), and miloxacin ( Horie and Nakazawa, 1992 ; Ueno and Aoki, 1996 ; Ueno et al, 2001 ).…”
Section: Introductionmentioning
confidence: 99%